FACTORS AFFECTING INTERNATIONAL JOINT VENTURE’S FINANCIAL PERFROMANCE IN THE PEOPLE’S REPUBLIC OF CHINA - Eliasson, Aleksi (My University, 2019)
The foreign direct investment inflow to China has in the recent decades experienced major developments. Foreign companies have noticed the potential of the Chinese business environment for not only its reduced labor costs compared to many western countries, but also for its high technological advancements and the new sources of income it offers to foreign companies. Because of this, FDI and China has gained interest among scholars. Especially the performance of international joint ventures has been a popular topic among researchers, for its complexity and the history that foreign investors and China has with joint ventures. This thesis aims to explain the reasons why some international joint ventures fail and others succeed from the financial perspective. This is examined through ten independent variables that includes both categorical and continuous variables as well as partner and host country related factors. These factors are used to determine their effect on the dependent variable, which in this thesis is net income. Based on the results, this thesis aims to create a roadmap for future international joint ventures, trying to access new sources of income. Based on existing studies and theories, multiple hypotheses are developed in order to further analyze the topic at hand. For the empirical part of the study, data of over 1000 international joint ventures was collected from a financial institution, which was then reduced to a sample of 186 joint ventures. This data was further analyzed through linear regression using IBM SPSS. The results indicate that an increase in capital investment to the joint venture increases the expected net income of the venture. Thus foreign companies should consider committing to their market entry to China with substantial investments. Successfully entering the Chinese markets requires large initial entry investments, especially in the case of western companies, who might not have an existing network in place. Partnering with a local company through a joint venture helps foreign companies get quicker access to local entities. The results also implied that obtaining sufficient funds could be accomplished though joining up with multiple partners. The amount of partners correlates positively with capital invested and thus, also has an indirect effect on joint venture performance. This study also found that joint ventures located in the central provinces of China, are expected to make larger profits than ventures located in the coastal or western provinces. Furthermore, the analysis shows that service companies are better equipped to succeed in the Chinese markets, than manufacturing companies. This study further advances the research conducted to understand what helps joint ventures succeed, by connecting multiple variables on the financial performance of an international joint venture. These findings provide new information for future researchers as well as companies striving to enter the Chinese markets.
Keywords: Joint venture performance; foreign direct investment; China; international joint venture; foreign market entry; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|